2024
DOI: 10.3390/cancers16050880
|View full text |Cite
|
Sign up to set email alerts
|

Supplement Use and Increased Risks of Cancer: Unveiling the Other Side of the Coin

Parnian Jabbari,
Omid Yazdanpanah,
David J. Benjamin
et al.

Abstract: There is a rising trend in the consumption of dietary supplements, especially among adults, with the purpose of improving health. While marketing campaigns tout the potential health benefits of using dietary supplements, it is critical to evaluate the potential harmful effects associated with these supplements as well. The majority of the scarce research on the potential harmful effects of vitamins focuses on the acute or chronic toxicities associated with the use of dietary supplements. Quality research is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…As a trace element, Se is crucial for numerous biological activities, such as thyroid hormone metabolism, antioxidant defense, immune system strengthening, and prevention of certain types of cancer [ 9 ]. Epidemiological studies have shown a negative correlation between Se intake and mortality from various cancers [ 10 ]. Se is primarily obtained from food sources and some Se supplements, including plants, animals, and certain microorganisms [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a trace element, Se is crucial for numerous biological activities, such as thyroid hormone metabolism, antioxidant defense, immune system strengthening, and prevention of certain types of cancer [ 9 ]. Epidemiological studies have shown a negative correlation between Se intake and mortality from various cancers [ 10 ]. Se is primarily obtained from food sources and some Se supplements, including plants, animals, and certain microorganisms [ 11 ].…”
Section: Introductionmentioning
confidence: 99%